-83-9x+x=101

Simple and best practice solution for -83-9x+x=101 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -83-9x+x=101 equation:


Simplifying
-83 + -9x + x = 101

Combine like terms: -9x + x = -8x
-83 + -8x = 101

Solving
-83 + -8x = 101

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '83' to each side of the equation.
-83 + 83 + -8x = 101 + 83

Combine like terms: -83 + 83 = 0
0 + -8x = 101 + 83
-8x = 101 + 83

Combine like terms: 101 + 83 = 184
-8x = 184

Divide each side by '-8'.
x = -23

Simplifying
x = -23

See similar equations:

| (12k^4)+(5k^2)-2=0 | | X+13x+40=0 | | 4x-50-10x=22 | | 6y-25=125 | | 4x-5p-10x=22 | | -10x-154-5x=41 | | 6y^2-7y+7=0 | | f(8)=(2x-8) | | -50=-t^2-5t | | 8x^2-21xy-9y^2=0 | | 3a+5=-28 | | 5w-5=5w+5 | | 36x+2=4 | | 2-16t=(-3t+2) | | 0.13y+0.05(y+6000)=1380 | | 18r=24r^2 | | 15y^2-15y+7=0 | | 2p(6p-18)=0 | | (x-9)(2x+4)=0 | | 25x^2/(5x-2) | | 7x-3=67forx | | 12x+72-30= | | 3h^2+6h=0 | | -3/7x=-6 | | f(5)=(2x-8) | | 16x^4+22x^3-4x^2= | | 4x^2-1x+1=0 | | 3x√35/7 | | 6m^5/2m^2 | | 2(X-15)=X/2 | | f(4)=(2x-8) | | 4x^2-1=63 |

Equations solver categories